Revitalization of regular landscape compositions of the park-monument of landscape art «Sharivskyi» - Maksymenko , Nadiya; Gololobova, Olena; Gololobov, Vadym; Kireyeu, Viktar (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Introduction. The perception of the landscape as a space for living has led to the formation and development of a special group of anthropogenic landscapes, namely garden and park landscapes, which are characterized by a wide range of functions from utilitarian to aesthetic and spiritual. Currently, approximately 30% of cultural heritage sites are in disrepair, and 80% require serious restoration work. Therefore, the revitalization of the landscape structure of historical garden and park landscapes is an urgent scientific problem and meets two sustainable development goals (goal 11 Sustainable cities and communities and goal 15 - Life on land). The purpose of article. To substantiate the concept of revitalization of regular landscape compositions of the park-monument of landscape gardening art of national importance "Sharivskyi" and to provide a graphic 3D model of architectural, planning and volumetric-spatial solutions of the proposed concept of revitalization of regular compositions of the studied landscape. Research methods. Method of historical analysis: with a focus on the period of the highest embodiment of the artistic compositional intent of the restored space, when the estate belonged to the successful sugar producer Leopold Koenig. The graphic presentation of architectural, planning, and three-dimensional solutions of the proposed revitalization concepts for the studied landscapes was achieved through the use of QGIS 3.28.3-Firenze 2022-08-31, Sketchup, and Realtime Landscaping Architect software tools. Main findings. In order to preserve the original idea and characteristics of the landscape compositions, the concept of revitalization of the White Garden was proposed, which was suggested by the "Genius loci" of the historical landscape of Sharivsky Park. Using the QGIS geographic information system, OSM standard map and Google Satellite Hybrid map, the 3D authentic relief of regular landscape compositions of the Sharivsky Palace and Park Complex was modeled. Using the Sketchup 2020 software tool, a graphical representation of the architectural, planning, and three-dimensional solutions of the studied historical landscape was made. The Sketchup 2020 software tool was also used for the graphic 3D reconstruction of numerous architectural details that adorn the palace, including balustrades, windows, doors, and towers decorated with ornaments. The dendrological plan was developed using species and cultivars of ornamental plants with identified historical and aesthetic value to ensure the continuity of new and preserved plant elements of landscape compositions. Scientific novelty and practical value. The proposed vision of preserving the sustainable features of the place, the selection of plants with identified historical and substantiated aesthetic value can be used in the complex reconstruction of regular garden and park landscapes of the Sharivskyi Park, a monument of landscape gardening art of national importance.